Phase II Study Evaluating PegLiposomal Doxorubicin and Carboplatin Combination Chemotherapy in Gynecologic Sarcomas and Mixed Epithelial-Mesenchymal Tumors A Phase II Protocol of the Arbeitsgemeinschaft Gynaekologische Onkologie Study Group (AGO-GYN 7). Issue 9 (November 2016) - Harter, Philipp; Sehouli, Jalid; Reuss, Alexander; Baumann, Klaus; Hanker, Lars; Kimmig, Rainer; Schröder, Willibald; Burges, Alexander; Gropp-Meier, Martina; Kurzeder, Christian; Mahner, Sven; Canzler, Ulrich; et al.
Abstract : Background: Gynecologic sarcomas are rare diseases with still undefined optimal treatment. Platinum and anthracyclines were reported as active agents in gynecologic sarcoma and carcinosarcoma. So far, data regarding the combination of carboplatin and pegylated liposomal doxorubicin for this patient population are missing. Methods: This prospective single-arm multicenter phase II trial evaluated the efficacy of carboplatin AUC 6 in combination with pegylated liposomal doxorubicin 40 mg/m 2 q28 in 40 patients with newly diagnosed or recurrent gynecologic sarcoma or carcinosarcoma. Results: Twenty patients with carcinosarcoma and 20 patients with leiomyosarcoma or endometrial stromal sarcoma were included. The percentage of patients with grade 3/4 neutropenia was 50%, but we did not observe any febrile neutropenia. The rates of grade 1 and 2 palmo-plantar erythema were moderate with 25% and 10%, respectively. Response rate was 33.3%. The 12-month progression-free and overall survival times were 32.5% and 77.0%, respectively. Conclusions: The combination of carboplatin and pegylated liposomal doxorubicin is feasible and has activity within the investigated study cohort.